Towards Resilient Organizations and Societies
XXIX, 336 p. 18 illus., 10 illus. in color.
Keywords: This open access book brings together scholars in the fields of management, public policy, regional studies, and organization theory around the concept of resilience. The aim is to provide a more holistic understanding of the complex phenomenon of resilience from a multi-sectorial, cross-national, and multidisciplinary perspective. The book facilitates a conversation across diverse disciplinary specializations and empirical domains. The authors contribute both to theory testing and theory development and provide key empirical insights useful for societies, organizations, and individuals experiencing disruptive pressures, not least in the context of a post-COVID-19 world. Diverse chapters are held together by a clear organization of the volume across levels of analysis (resilience in organizations and societies) and by an original perspective on resilience derived from an extended review, by the editors, of the existing literature and knowledge gaps, according to which each of the individual chapter contributions is positioned and connected to. Rómulo Pinheiro is Professor of Public Policy and Administration at the Department of Political Science and Management at the University of Agder, Norway. Maria Laura Frigotto is Associate Professor in Organization Theory and Management at the Department of Economics and Management at the University of Trento, Italy. Mitchell Young is Assistant Professor in the Department of European Studies, Institute of International Studies at Charles University, Czech Republic. .